2020
DOI: 10.7150/thno.36220
|View full text |Cite
|
Sign up to set email alerts
|

Mdig promotes oncogenic gene expression through antagonizing repressive histone methylation markers

Abstract: The mineral dust-induced gene (mdig) is overexpressed in a number of human cancers, suggesting critical roles of this gene played on the pathogenesis of cancers. Unlike several other JmjC-domain containing proteins that exhibit histone demethylase activity, it remains enigmatic whether mdig is involved in the demethylation processes of the histone proteins.Methods: To provide direct evidence suggesting contribution of mdig to the demethylation of histone proteins, we recently examined the histone methylation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…Methylation at different histone residue sites gives distinct impact on transcriptional activity and high-order chromatin structure. Proper control of H3K27me3 level and its distribution pattern across different genomic features are essential for embryonic development and maintenance of physiological homeostasis, which frequently goes awry during tumorigenesis 12 , 37 , 38 . Therefore, the feasibility of targeting molecules keeping the balance of H3K27me3 for cancer therapeutics has been under evaluation for a long time, such as EZH2 inhibitors 14 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Methylation at different histone residue sites gives distinct impact on transcriptional activity and high-order chromatin structure. Proper control of H3K27me3 level and its distribution pattern across different genomic features are essential for embryonic development and maintenance of physiological homeostasis, which frequently goes awry during tumorigenesis 12 , 37 , 38 . Therefore, the feasibility of targeting molecules keeping the balance of H3K27me3 for cancer therapeutics has been under evaluation for a long time, such as EZH2 inhibitors 14 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the most relevant selection signal in the AFT/North AFT comparison (BTA06 at position: 46,780,000-50,050,000 bp) harboured one protein coding gene (PCDH7) which coincides with a known CNV ( Supplementary Table S4), one 5S ribosomal RNA (5S rRNA) and three non-coding RNA genes: SNORA70, Y_RNA and U6 (Table 1). PCDH7 is one of the key genes involved in oncogenesis and/or differentiation of the cancer stem cells through a change in its histone methylation status 49 . Likewise, 5S rRNA genes are highly methylated in Arabidopsis thaliana and their expression is under epigenetic control 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from SUV39H1/2, it is also possible that other upstream regulators of SUV420H2 such as HP1 may have an unidentified role in mediating resistance to drugs, such as EGFRi (Bosch-Presegué et al, 2017;Hahn et al, 2013). Indeed, the first identified demethylase for H4K20me3, mineral dust-induced gene (Mdig) was determined to be overexpressed in breast and lung cancer cells antagonizing the effects of the H4K20me3 modification which led to induction of oncogenes (Zhang et al, 2020). Analogous to Mdig overexpression in cancer cells, leading to reduction of H4K20me3, we found that loss of SUV420H2 also leads to depletion of H4K20me3 mark that in turn enhances oncogenes such as LINC01510 and MET.…”
Section: Discussionmentioning
confidence: 99%